(untitled) (Bangladesh Journal of Dental Research & Education, 2013)
With over 400 bacterial species the periodontal microbiota has clearly a diverse ecology and uncultivated organisms are found to be associated with the periodontal diseases. Many efforts have been made to determine why so many bacterial species cannot be cultured on conventional bacteriological media and to develop new cultural methods for their isolation. In recent years, metagenomic analysis is available, based on the direct examination of nucleic acids from samples.This review will address the new dimensions of this novel procedure which will lead to a better understanding of the role of oral microbiota in periodontal disease. DOI: http://dx.doi.org/10.3329/bjdre.v3i2.16611 Bangladesh Journal of Dental Research & Education Vol.3(2) 2013: 36-40